Mechanism Of Neural Precursor Cell Expressed Developmentally Down-Regulated 4-Like (Nedd4l) In Modulating Ferroptosis Via Ubiquitination Of Solute Carrier Family 7 Member 11 (Slc7a11) In Oesophageal Squamous Cell Carcinoma - Chen, Zhen (2024)
Detecting oesophageal squamous cell carcinoma (oscc) in early stages poses significant challenges due to its subtle presentation. The absence of approved targeted therapies and poor prognosis further compound the difficulties in treating oscc. Ferroptosis, with its capacity to inhibit the proliferation of cancer cells, highlights potential in cancer therapy, and its combination with chemotherapy may improve treatment effectiveness. Emerging evidence showed that nedd4l is an e3 ubiquitin ligase that plays a curial role in tumour suppression by regulating ferroptosis pathway through ubiquitination. However, their relationship and specific regulatory mechanism in oscc remains unknown. Therefore, this study was designed to elucidate the role of nedd4l in oscc, as well as the specific regulatory mechanism between nedd4l and ferroptosis in oscc. The small interfering rna was used first to investigate the impact of silencing nedd4l on oscc. The results showed that silencing nedd4l accelerated the migration and invasion of ec9706 cells, as well as promoted the proliferation of ec9706 and eca109 cells. Xenograft mouse models were established through the subcutaneous injection of ec9706 cells infected with short hairpin nedd4l. After 30 days, the tumour weight and volume of the mice were measured and the results confirmed that silencing nedd4l triggered tumour growth in oscc.